The cost of a single concussion in American high school football: a retrospective cohort study - Aaron M Yengo-Kahn; Patrick D Kelly; David C Liles; Lydia J McKeithan; Candace J Grisham; Muhammad Saad Khan; Timothy Lee; Andrew W Kuhn; Christopher M Bonfield; Scott L Zuckerman (Concussion)
Aim: The potential financial burden of American football-related concussions (FRC) is unknown. Our objective was to describe the healthcare costs associated with an FRC and determine factors associ...